2010
DOI: 10.1136/adc.2009.179416
|View full text |Cite
|
Sign up to set email alerts
|

Nasal trauma due to continuous positive airway pressure in neonates

Abstract: Nasal trauma is a frequent complication of nCPAP, especially in preterm neonates, but long-term cosmetic sequelae are very rare. This study provides a description of nasal trauma and proposes a simple staging system. This could serve as a basis to develop strategies of prevention and treatment of this iatrogenic event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
7
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(183 citation statements)
references
References 21 publications
(28 reference statements)
12
161
7
3
Order By: Relevance
“…We observed more frequent and more severe skin compromise than previous reports of 49% with mostly transient or persistent erythema 28 and 88% stage I pressure ulcers in neonates using masks. 29 Our larger skin hydration differences were associated with visible erythema, as reported by others. 30 Hydration was greater for erythema than normal skin and higher for stage I pressure ulcers than erythema.…”
Section: Discussionsupporting
confidence: 68%
“…We observed more frequent and more severe skin compromise than previous reports of 49% with mostly transient or persistent erythema 28 and 88% stage I pressure ulcers in neonates using masks. 29 Our larger skin hydration differences were associated with visible erythema, as reported by others. 30 Hydration was greater for erythema than normal skin and higher for stage I pressure ulcers than erythema.…”
Section: Discussionsupporting
confidence: 68%
“…Nasal injuries were evaluated according to the classification proposed by Buettiker et al, [11] who described the severity of nasal trauma secondary to nCPAP in neonates. Nasal injuries were classifi ed as mild, moderate, and severe.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Yong et al [10] reported an incidence of 35% for nasal trauma in the prongs group. Fischer et al [11] found that 420 (42.5%) of 989 patients developed a nasal trauma. Gunlemez et al [12] demonstrated that the silicon gel on the surface of the nostrils reduced the incidence of nasal injury in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Five studies involving 857 infants 21,29,33,38,40 revealed the incidence of nasal trauma in infants supported on HHHFNC compared with other forms of NIV. One more trial 26 revealed nasal trauma, but as scores rather than events, and could not be included in the analysis.…”
Section: Nasal Traumamentioning
confidence: 99%